HAROLD PINTER: FROM POETICS TO POLITICS - Dilek İNAN (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Harold Pinter was giuen the Nobel Prize for Literatüre in 2005 for his contributions to British and contemporary drama. Pinter has been a theatrical institution for half a century, he has revolutionised his theatre fay being a conscientious objector in public and a political actiuist since the 1980s. He has explored different genres including prose and poetry, plays for stage, radio and screen. His crossover from one medium to another, his deliberate decision to mite for more than one medlum, has given him the opportunity to reach the potential mass audience. He has shocked beuuildered, disappointed, and astonished audiences and critics. He sıviftly became accepted as Britain’s premier dramatist. This paper traces the evolution that Pinter has gone through from the early 1950s until the 2000s. Additionally, the paper identifies Harold Pinter's ‘Pinteresque' style - a term ıvhich enters English Language and Literatüre after him and also exemplify and reason Pinter’s change in his style from poetical to political. --- İngiliz ve Dünya Tiyatrosuna katkılarından dolayı 2005 yılında Harold Pinter’a Nobel Edebiyat ödülü verilmiştir. Pinter yanm asırdır tiyatroya hizmet etmektedir, 1980lerden günümüze kadar, tiyatro kimliğini politik kimliğiyle zenginleştirmiştir. Yarım asırlık dönemde, düzyazı, şiir, tiyatro oyunu, radyo oyunu ve film senaryosu gibi farklı türlerde eserler üretmiştir. Edebiyat türleri arasındaki geçişleri ve değişimleri O’nun her zaman daha fazla izleyici kitlesine ulaşmasına imkân vermiştir. Edebiyat eleştirmenlerini ve izleyicileri şaşırtmış, büyülemiş, kızdırmış hatta hayal kırıklığına uğratmıştır. Kısa zamanda İngiliz Tiyatrosunun en önde gelen yazan olmuştur. Bu çalışma, 1950-2000 yılları arasında geçen bir üretkenliğin evrimini ve ‘Pinteresque’ kavramını İngiliz Dili ve Edebiyatına kazandıran Harold Pinter’ın yazarlık hayatında şiirsel ve gizemli başlayan üslubunun giderek artan politik söylemlerinin örneklerini ve nedenlerini izleyecektir.